Use of ICT Systems in Handling Monetary Civil Claims in Poland and England (United Kingdom): A Comparative Analysis - Skawiński, Franciszek (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The article aims to compare how ICT systems are used in handling monetary civil claims in Poland and England through an analysis of both legal and technical regulations and limitations. This objective is achieved through critical analysis of existing literature together with the official documentation available for both systems, as well as direct inspection of the systems. As a result of said analysis, it is apparent that the system utilised in England, despite being significantly older than the Polish system, has much more technical limitations, although they are also clearly specified in the relevant law. On the other hand, some such limitations in the Polish system are not present anywhere in statute law. Nevertheless, both systems seem to be mainly designed for handling smaller claims and reducing the amount of mainly administrative labour that was usually done manually by the court staff. In conclusion, some de lege ferenda propositions and future suggestions were formulated for both systems arising chiefly from the results of the comparative analysis.